Targeted Therapy of Papillary Thyroid Cancer: A Comprehensive Genomic Analysis - Hescheler, Daniel A.; Riemann, Burkhard; Hartmann, Milan J. M.; Michel, Maximilian; Faust, Michael; Bruns, Christiane J.; Alakus, Hakan; Chiapponi, Costanza (Frontiers in Endocrinology, 2021)
Abstract Background: A limited number of targeted therapy options exist for papillary thyroid cancer (PTC) to date. Based on genetic alterations reported by the "The Cancer Genome Atlas (TCGA)", we explored whether PTC shows alterations that may be targetable by drugs approved by the FDA for other solid cancers. Methods: Databases of the National Cancer Institute and MyCancerGenome were screened to identify FDA-approved drugs for targeted therapy. Target genes were identified using Drugbank. Genetic alterations were classified into conferring drug sensitivity or resistance using MyCancerGenome, CiViC, TARGET and OncoKB. Genomic data for PTC were extracted from TCGA and mined for alterations predicting drug response. Results: 129 FDA approved drugs with 128 targetable genes were identified. 196 (70%) of 282 classic, 21 (25%) of 84 follicular and all 30 tall cell variant PTCs harbored druggable alterations: 259 occurred in 29, 39 in 19 and 31 in 2 targetable genes, respectively. The BRAF V600 mutation was seen in 68% of classic, 16% of follicular variant and 93% of tall cell variant PTCs. The RET gene fusion was seen in 8% of classic PTCs, NTRK1 & 3 gene fusions in 3% and other alterations in <2% of classic variant PTCs. 99 of 128 (77%) FDA approved targetable genes did not show any genetic alteration in PTC. Beside selective and non-selective BRAF-inhibitors, no other FDA-approved drug showed any frequent predicted drug sensitivity (<10%). Conclusion: Treatment strategies need to focus on resistance mechanisms to BRAF inhibition and on genetic alteration independent alternatives rather than on current targeted drugs.